2019
DOI: 10.1099/acmi.0.000020
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal puerperal mastitis in a lactating mother

Abstract: Introduction A case of pneumococcal mastitis in a breast-feeding mother 6 months postpartum is described. Mastitis is usually caused by Staphylococcus aureus . A review of the literature from 1950 to March 2018 revealed only four other cases in which the causative organism was Streptococcus pneumoniae . Case presentation The nursing mother presented with high fever and the four cardinal signs of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Two cases7 8 showed that an infected child could cause S. pneumoniae mastitis in the mother. Four other cases9–12 suggested an association with S. pneumoniae mastitis, even if the child was asymptomatic. The exact mechanism underlying this infection remains unclear; however, both host and pathogen factors are thought to play a key role 16.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Two cases7 8 showed that an infected child could cause S. pneumoniae mastitis in the mother. Four other cases9–12 suggested an association with S. pneumoniae mastitis, even if the child was asymptomatic. The exact mechanism underlying this infection remains unclear; however, both host and pathogen factors are thought to play a key role 16.…”
Section: Discussionmentioning
confidence: 98%
“…Pneumococcal non-lactational mastitis has rarely been reported in patients with underlying diseases, such as systemic lupus erythematosus; however, reports of pneumococcal lactational mastitis are scarce, with only six cases reported in the English literature between 1995 and 2021 (table 1). 7–12…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Debemos destacar dos casos de mastitis lactacional y uno de fascitis necrotizante. La mastitis lactacional neumocócica es excepcional, habiéndose descrito 5 casos desde 1995 [13][14][15]. En todos ellos, S. pneumoniae se aisló en los cultivos de leche materna, y su presencia se atribuyó a la transmisión desde el niño en el momento del amamantamiento.…”
Section: Materials Y Métodosunclassified